DOCK8 functions as an adaptor that links TLR-MyD88 signaling to B cell activation - BARIŞ, SAFA (NATURE PUBLISHING GROUP, 2012)
The adaptors DOCK8 and MyD88 have been linked to serological memory. Here we report that DOCK8-deficient patients had impaired antibody responses and considerably fewer CD27(+) memory B cells. B cell proliferation and immunoglobulin production driven by Toll-like receptor 9 (TLR9) were considerably lower in DOCK8-deficient B cells, but those driven by the costimulatory molecule CD40 were not. In contrast, TLR9-driven expression of AICDA (which encodes the cytidine deaminase AID), the immunoglobulin receptor CD23 and the costimulatory molecule CD86 and activation of the transcription factor NF-kappa B, the kinase p38 and the GTPase Rac1 were intact. DOCK8 associated constitutively with MyD88 and the tyrosine kinase Pyk2 in normal B cells. After ligation of TLR9, DOCK8 became tyrosine-phosphorylated by Pyk2, bound the Src-family kinase Lyn and linked TLR9 to a Src-kinase Syk-transcription factor STAT3 cascade essential for TLR9-driven B cell proliferation and differentiation. Thus, DOCK8 functions as an adaptor in a TLR9-MyD88 signaling pathway in B cells.
Keywords: SYK TYROSINE KINASE; TOLL-LIKE RECEPTORS; NF-KAPPA-B; IMMUNE-RESPONSES; ANTIBODY-RESPONSES; HUMORAL IMMUNITY; STAT3 ACTIVATION; CPG ODN; INDUCTION; MYD88